Maternal mortality in times of the COVID-19 pandemic: An integrative review (Research, Society and Development, 2022)
This article aims to analyze publications on maternal mortality in times of COVID-19 and determine the impacts suffered in this recent panorama motivated by this pandemic. For this, an integrative review was conducted with a survey of material in the repository Virtual Health Library, Medline, Lilacs and Scielo. Filtering the material according to pre-established criteria, six articles remained for analysis. As results, preliminary impacts were evidenced, such as fragility in the access and care of the studied group, the lack of adequate treatment for fear of pregnant and postpartum women to seek assistance and increase in maternal deaths caused, directly or indirectly, by the pandemic.